Bringing scientific rigor to community-developed programs in Hong Kong - Fabrizio Cecilia S; Hirschmann Malia R; Lam Tai Hing; Cheung Teresa; Pang Irene; Chan Sophia; Stewart Sunita M (BMC, 2012)
Abstract Background This paper describes efforts to generate evidence for community-developed programs to enhance family relationships in the Chinese culture of Hong Kong, within the framework of community-based participatory research (CBPR). Methods The CBPR framework was applied to help maximize the development of the intervention and the public health impact of the studies, while enhancing the capabilities of the social service sector partners. Results Four academic-community research teams explored the process of designing and implementing randomized controlled trials in the community. In addition to the expected cultural barriers between teams of academics and community practitioners, with their different outlooks, concerns and languages, the team navigated issues in utilizing the principles of CBPR unique to this Chinese culture. Eventually the team developed tools for adaptation, such as an emphasis on building the relationship while respecting role delineation and an iterative process of defining the non-negotiable parameters of research design while maintaining scientific rigor. Lessons learned include the risk of underemphasizing the size of the operational and skills shift between usual agency practices and research studies, the importance of minimizing non-negotiable parameters in implementing rigorous research designs in the community, and the need to view community capacity enhancement as a long term process. Conclusions The four pilot studies under the FAMILY Project demonstrated that nuanced design adaptations, such as wait list controls and shorter assessments, better served the needs of the community and led to the successful development and vigorous evaluation of a series of preventive, family-oriented interventions in the Chinese culture of Hong Kong.